Highly conductive solid polymer-(ionic liquid) electrolytes prepared by in situ photopolymerization - Andrzejewska, E.; Stępniak, I. (Polimery, 2022)
Solid polymer electrolytes containing ionic liquids (ILs) were prepared by the photopolymerization of monomer-IL homogenous mixtures. This methods enables the preparation of solid polymer electrolytes in reaction carried out at room temperature in the time of about 10 min. The appropriate selection of the substrate allowed to obtain the high ionic conductivity of the solid polymer electrolytes (of the order of 10-3 - 2ź10-2 S/cm), in some cases exceeding the conductivity of the ionic liquid used.